Reformulating the Green Economy Through the Perspective of Jasser Auda's Maqāṣid al-Syarī’ah as a Contemporary Solution - Makraja, Fahmi; Azmi, Ulil; Farhan, Zhafirah Rizqa (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2026)
This study examines the urgency of reconstructing the green economy concept through the maqāṣid al-syarī’ah framework developed by Jasser Auda. The research employs a qualitative method with a systematic-integrative literature review approach to synthesize Auda’s systems theory with contemporary green economic indicators. Data was collected from primary sources, specifically Auda’s seminal works, and secondary peer-reviewed journals, which were then analyzed using qualitative content analysis. Jasser Auda’s systems approach incorporating features such as wholeness (kulliyyah), openness (infitāḥiyyah), and multi-dimensionality serves as the systematic analytical framework to evaluate the ethical and philosophical foundations of the green economy. The study finds that conventional interpretations of maqāṣid are often static and fragmentary in addressing ecological crises. Through this systemic framework, the green economy is reconstructed into a model that is not only economically efficient but also ecologically responsible and socially just. This research concludes that the integration of a systems-based maqāṣid provides a comprehensive and operational solution for sustainable development in the contemporary era.